CERAI GUGAT TERHADAP SUAMI PENGGUNA NARKOBA DI PENGADILAN AGAMA PADANG KELAS 1A - Mardius, Harry Susanto Putra dan (Fakultas Hukum Universitas Tamansiswa Padang, 2022)
The divorce that occurred in the decision Number 0174/Pdt.G/2015/PA.Pdg. who reported to the religious court that the wife filed for divorce from her husband because it was known that the husband was consuming drugs or illegal drugs can damage the minds of users and drugs and drugs are the mother of all forms of crime that can be deadly. Divorce is a divorce that occurs at the request of the wife by giving a ransom to and with the approval of her husband, according to article 77 of law number 7 1989 in conjunction with law number 3 of 2006 in conjunction with law number 50 of 2009 filed by the wife as a plaintiff or her attorney to the court religion whose legal area includes the residence of the wife as the plaintiff, unless the wife as the plaintiff intentionally leaves the joint residence without the husband's permission as the defendant. From the results of research conducted regarding the implementation of divorce lawsuits against husbands of drug users, the decision number 0174/Pdt.G/2015/PA.Pdg starts from filing a divorce suit, witnesses, examination and reconciliation of divorce lawsuits and court decisions regarding the dissolution of marriage due to a divorce lawsuit. Because this case is a civil case which is subject to a special procedural law case, based on the lexspecialis derogat lex generalis principle, even though the aquo case is examined and decided by verstek, the plaintiff is still burdened with mandatory evidence. So the judge's consideration in deciding the decision number 0174/Pdt.G/2015/PA.Pdg, namely stating that the defendant who had been officially summoned and deserved to appear before the trial was not present, granted the plaintiff's claim with verstek, handed down the divorce of one ba'in of the defendant against the plaintiff.